Fairy tale - Teverson, Andrew (Routedge, 2013)
Introduction -- Definitions -- The emergence of a literary genre: early modern Italy to the French salon -- The consolidation of a genre: the brothers Grimm to Hans Christian Andersen -- The emergence of fairy-tale theory: Plato to Propp -- Psychoanalysis, history and ideology: twentieth- and twenty-first century approaches to fairy tale -- Conclusion.; Includes bibliographical references (pages 152-159) and index